Semi-field experiments reveal contrasted predation and movement patterns of aquatic macroinvertebrate predators of Anopheles gambiae larvae - Hudson Onen; Emmanuel W. Kaindoa; Joel Nkya; Alex Limwagu; Martha A. Kaddumukasa; Fredros O. Okumu; Jonathan K. Kayondo; Anne M. Akol; Frédéric Tripet (Malaria Journal)
Abstract Background Members of the Anopheles gambiae complex are major malaria vectors in sub-Saharan Africa. Their larval stages inhabit a variety of aquatic habitats in which, under natural circumstances, they are preyed upon by different taxa of aquatic macroinvertebrate predators. Understanding the potential impact of predators on malaria vector larval population dynamics is important for enabling integrated local mosquito control programmes with a stronger emphasis on biocontrol approaches. This study experimentally evaluated the predation efficacy and foraging strategy of three common aquatic macroinvertebrate predators of An. gambiae, diving beetles (Coleoptera), backswimmers (Hemiptera), and dragonfly nymphs (Odonata) in a semi-field system in South-Eastern Tanzania. Methods An array of alternating small and large basins used as aquatic habitats was created in two compartments of a semi-field system and filled with well water. Field-collected adult diving beetles, backswimmers or dragonfly nymphs were randomly assigned to these habitats and Anopheles arabiensis larvae were added as prey in half of the habitats. The number of mosquito larvae consumed, predator mobility across habitats and mortality were recorded at 24, 48 and 72 h. Results The presence of An. gambiae larvae in habitats significantly increased the survival of backswimmer and dragonfly nymphs, which are not mobile. In contrast, diving beetles survived well under any initial condition by preferentially flying away from habitats without prey to nearby larger habitats with prey. The larval predation rates of predacious diving beetle, backswimmer and dragonfly nymphs were stable over time at a mean of 3.2, 7.0 and 9.6 larvae consumed each day. Conclusion This study demonstrates that aquatic macroinvertebrate predators display adaptive foraging behaviour in response to prey presence and aquatic habitat size. It also confirms the ability of these predators to significantly reduce An. gambiae larval densities in aquatic habitats, thus their potential for consideration as additional biocontrol tools for mosquito population reduction.